Academic library leadership in the digital age. Issue 4 (8th June 2015) - Le, Binh P.
Abstract : Purpose: – The purpose of this paper is to focus on academic library leadership in the digital age. Primarily, the goals are to identify: first, the top five major challenges facing academic library leadership; second, the top five most important leadership skills required for effective academic library leadership; and finally, the top five best ways to develop these academic library leadership skills. Design/methodology/approach: – A survey was conducted to elicit responses from individuals who hold senior library leadership positions in American academic libraries throughout the USA. The participants were identified through several means: the web sites of the ALA and its divisions; the web sites of American universities; referrals; and the author's professional contacts. To simplify the survey research process, e-mails including the survey research questions were sent to potential participants. In all, 38 invitations ( n =38) were sent out to large and medium-size academic libraries throughout the USA. Over 36.8 percent ( n =14) of the participants returned the survey. The participants represent a wide spectrum of libraries. Findings: – The top five major challenges are how to: demonstrate the library values to the university community, operate the library under fiscal uncertainty, retrofit outdated library facilities to accommodate new services, strike a balance between digital and print materials, and keep the library staff trained and current. The top five essential academic library leadership attributes are: vision, integrity, management skills, collaboration skills, and communication skills. The top five best ways to acquire these skills include the need to have mentors, to attend leadership development programs, to gain practical library leadership experience, to seek leadership roles, and to know oneself. Originality/value: – Research in this area is rather limited. As a result, this study will contribute to the academic library leadership literature and help current and aspiring academic library leaders worldwide with insightful leadership lessons needed to lead academic libraries successfully in this transformational era.